دور الاستثمار في تنمية الصناعة التحويلية (Latakia University Journal - Economic and Legal Sciences Series, 2018)
In this research study the role of investment, both public and private sectors in the development of the manufacturing industry in Syria, through a set of indicators and statistical data for the industry, this study showed that investment a significant role adult impact in the industry, where the investment decline in recent years of the study the rates of negative growth, in light of public investment fell after he occupied the largest proportion of investment and increased private investment role. the study also showed that the decline in investment had a negative impact on all industry indicators manufacturing in Syria, in terms of reduced its contribution to net GDP Of the total, and the private sector with the largest proportion of the public sector in its contribution to the net gross domestic product manufacturing, with a deficit in the trade balance of manufacturing, with the observation that the number of workers in the manufacturing industry occupies the largest proportion of about 70%, but it began to decline. تم في هذا البحث دراسة دور الاستثمار بشقيه العام والخاص في تنمية وتطوير الصناعة التحويلية في سورية  , من خلال مجموعة من المؤشرات والبيانات الاحصائية الخاصة بهذه الصناعة , وبينت هذه الدراسة أن للاستثمار دور كبير وأثر بالغ في هذه الصناعة , حيث تراجع الاستثمار في السنوات الاخيرة من الدراسة وبمعدلات نمو سالبة , في ظل تراجع الاستثمار العام  بعد ان كان يحتل النسبة الأكبر من الاستثمار وتزايد دور الاستثمار الخاص ,  كما دلت الدراسة أن هذا التراجع في الاستثمار أثر سلبأ على جميع مؤشرات الصناعة التحويلية في سورية , من حيث انخفاض مساهمتها في صافي الناتج المحلي الاجمالي , والقطاع الخاص ذات النسبة الأكبر من القطاع العام في مساهمته في صافي الناتج المحلي الاجمالي للصناعة التحويلية ,  مع وجود العجز في الميزان التجاري للصناعة التحويلية , مع الملاحظة أن عدد العمال في الصناعة التحويلية تحتل النسبة الأكبر بحوالي 70% إلا انها بدأت بالتراجع .